Leader-Member Exchange Paradigm in RSUD Dr. Saiful Anwar Malang - Sutrisno, Timotius F.C.W; Teofilus, Teofilus; Silaswara, Diana; Rusmi, Nanduta Sito (Jurnal Manajemen Bisnis, 2021)
Research aims: The study was conducted to discuss the phenomenon of destructive leadership, cynicism, and employee performance that occurred at Dr. Saiful Anwar Malang Hospital. The purpose of this study is to look at the effect of destructive leadership on employee performance, the effect of cynicism on employee performance, and the moderation effect of cynicism on destructive leadership and employee performance at Dr. Saiful Anwar Malang Hospital.Design/Methodology/Approach: This study employed a partial least square (PLS) multivariate statistical technique. Sampling used a saturated sampling method, and the respondents were all employees of the Finance Department from 50 hospitals. The Likert scale was utilized as a measurement tool for the questionnaire.Research findings: This study's results indicated that the destructive leadership variable positively and significantly influenced the employee performance variable. Based on the questionnaire results, it was known that Dr. Saiful Anwar Malang Hospital’s employee performance had a positive nature in responding to the existence of destructive leadership so that performance was maintained.Theoretical contribution/Originality: Companies can develop strategies to anticipate destructive leadership and weaken cynicism because both attitudes can impact employee performance.Practitioner/Policy implication: This research is expected to provide insight into leaders’ and employees' behavior regarding the phenomenon of destructive leadership and cynicism to improve employee performance because companies with a positive culture can undoubtedly make employees comfortable so that they will do work optimally.Research limitation/Implication: This research’s implication shows that the employees’ behavior in Dr. Saiful Anwar Malang Hospital was very good because employees could show positive attitudes even with pressures, such as destructive leadership and cynicism.